The role of Toll-like receptor 4 signaling pathway in ovarian, cervical, and endometrial cancers - Lupi, Luiz Antonio [UNESP]; Cucielo, Maira Smaniotto [UNESP]; Silveira, Henrique Spaulonci [UNESP]; Gaiotte, Letícia Barbosa [UNESP]; Cesário, Roberta Carvalho [UNESP]; Seiva, Fábio Rodrigues Ferreira; de Almeida Chuffa, Luiz Gustavo [UNESP] (Elsevier, 2020)
Toll-like receptors (TLRs) are critical sensors related to inflammation and tumorigenesis. Among all subtypes, the TLR4 is a highly described transmembrane protein involved in the inflammatory process. The TLR4/myeloid differentiation factor 88 (MyD88) signaling pathway has been implicated in oncogenic events in several tissues and is associated with survival of patients. Through activation, TLR4 recruits adaptor proteins, i.e., MyD88 or TRIF, to triggers canonical and non-canonical signaling pathways that result in distinct immune responses. In most cancer cells, uncontrolled TLR4 signaling modifies the tumor microenvironment to proliferate and evade immune surveillance. By contrast, TLR4 activation can produce antitumor activities, thereby inhibiting tumor growth and enhancing the proper immune response. We review herein recent approaches on the role of the TLR4 signaling pathway and discuss potential candidates for gynecological cancer therapies; among these agents, natural and synthetic compounds have been tested both in vitro and in vivo. Since TLR4 ligands have been investigated as effective immune-adjuvants in the context of these aggressive malignancies, we described how TLR4 signaling controls part of the tumor-related inflammatory process and which are the new targeting molecules implicated in the regulation of tumorigenicity in ovarian, cervical, and endometrial cancers.
Keywords: Cervical cancer; Endometrial cancer; Immune system; Inflammation; Ovarian cancer; TLR4